The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/lra.2021.3070305
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Soft Robot Modeling and Control With Differentiable Simulation

Abstract: Underwater soft robots are challenging to model and control because of their high degrees of freedom and their intricate coupling with water. In this paper, we present a method that leverages the recent development in differentiable simulation coupled with a differentiable, analytical hydrodynamic model to assist with the modeling and control of an underwater soft robot. We apply this method to Starfish, a customized soft robot design that is easy to fabricate and intuitive to manipulate. Our method starts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 29 publications
(28 reference statements)
1
29
0
Order By: Relevance
“…However, this process requires intensive computation power and is very lengthy. New research proposes the use of differentiable simulation as a method of modeling soft robots and bridging the simulation-to-reality gap [21].…”
Section: Soft Pneumatic Actuator (Spa)mentioning
confidence: 99%
“…However, this process requires intensive computation power and is very lengthy. New research proposes the use of differentiable simulation as a method of modeling soft robots and bridging the simulation-to-reality gap [21].…”
Section: Soft Pneumatic Actuator (Spa)mentioning
confidence: 99%
“…However, exact gradients can be difficult to derive symbolically for complex optimization problems. Instead, recent works have turned to automatic differentiation using differentiable programming to automatically compute gradients in problems such as 3D shape optimization [18], aircraft design optimization [19], robot design optimization [20], [21], and machine learning [22].…”
Section: A Differentiable Simulation and Temporal Logicmentioning
confidence: 99%
“…In the past this would require black-box optimisation or calculation of numerical gradients but can now be achieved using gradients calculated using autodiff libraries. Examples of real2sim systemID include the optimisation of a pendulum start state and parameters [13], soft robot properties [14] and frictional properties [15]. However, one of the limiting factors for systemID using a differentiable simulator is the simulation time which has to be on the order of seconds or less.…”
Section: B Differentiable Simulatorsmentioning
confidence: 99%
“…Extending upon their earlier work Heiden et al [17] demonstrated the transference of a quadrupedal walking policy from simulation to a real quadruped using a large number of optimal trajectories generated from simulation. Another sim2real investigation conducted using differentiable simulators is work by Du et al where the authors implemented a sim2real approach for a underactuated underwater robot [14].…”
Section: B Differentiable Simulatorsmentioning
confidence: 99%